The perception of difference and the differences of perception: The image of the Norman invaders in southern Italy in contemporary western medieval and Byzantine sources - TOUNTA, Eleni (Byzantina Symmeikta, 2010)
The paper examines the image of the Norman invaders in southern Italy in contemporary western medieval and Byzantine sources. The comparative method and the methodology of linguistic and literary criticism are equally applied. The interest is focussed on the conceptual notions that defined the perception of the Norman invaders by medieval men and, consequently, their cultural representation. In this way, mentalities and social values are revealed, and, thus, historians investigating political developments are offered a research tool for medieval historical sources.